AM/PM dosing of LAMA for COPD: a randomized controlled trial protocol using digital recruitment and registries - Sivapalan, Pradeesh; Rømer, Valdemar; Wirenfeldt Klausen, Tobias; Dyrby Johansen, Niklas; Pareek, Manan; Modin, Daniel; Mathioudakis, Alexander; Vestbo, Jørgen; Eklöf, Josefin; Jordan, Alexander; Hurst, John R.; Biering-Sørensen, Tor; et al. (Frontiers in Medicine, 2024)
Long-acting muscarinic antagonists (LAMAs) reduces the risk of acute chronic obstructive pulmonary disease (AECOPD), usually taken once daily in the morning. However, the circadian activity of autonomic regulation suggests that the highest need for anticholinergic therapy may be in the late night/early morning. This is supported by evidence documenting that AECOPD most often begins in the morning. Furthermore, the trough spirometry effect of LAMA is lower than the peak effect, which further argues that evening dosing may be more optimal than morning dosing. This trial aims to determine whether evening administration of LAMA reduces hospitalization-requiring AECOPD or death from all causes within a one-year period as compared with morning administration of the same LAMA.Randomized controlled open-label trial. Persons aged 30 years or older with a once-daily LAMA prescription and confirmed COPD-diagnosis were recruited. Participants were randomized in a 1:1 ratio to either morning or evening LAMA-administration.Complete follow-up for the primary outcome, hospitalization-requiring AECOPD or death from all causes within one year, was captured from the Danish National Health Register, and from patient reported outcome assessments at 6 and 12 months.A total of 10,013 participants were randomized and the recruitment process started March 9, 2023.Secondary outcomes include i) moderate COPD exacerbations; ii) all-cause hospitalization; iii) ICUadmission; iv) need for non-invasive ventilation; v) all-cause mortality, among others. All outcomes will be evaluated 12 months after recruitment.